Addiction is one of the social problems which has a significant role in the spiritual and physical health of the person, family - Fereshte Jaliliyan (Drug Control Headquarters, Research and Education Office, 2009)
Addiction is one of the social problems which has a significant role in the spiritual and physical health of the person, family, and specially the health of the society. One of the main factors for continuance and intensity of involvement in addiction, is that the individuals, the network positive (healthy) relations is low. There fore, in this study, the role of the network positive (healthy) and the network negative (unhealthy) relations in degree (intensity) of the person's involvement in addiction is being considered. in this research the role of The variable of the informal social control is also considered as an intermediate is assumed on the degree of the involvement in addiction. Using measurement and questionnaire method, the hypotheses of the research is being tested. The statistical society people who were trying to abandon in the major centers for the abandonment of the addiction in Tehran (The center of Kongre 60 for the abandonment of addiction and Aftab society). The sample volume has been 120 people for selecting them, the method of simple accidental sampling is being used. Also the selection of the centers, among the centers for the abandonment of the addiction, has been in the simple accidental from and then using the technique of the structured interview, the information is collected and analyzed. The results of this study shows that how much higher is the individuals' the network negative (unhealthy) relation before and next addiction, the degree (intensity) of their involvement in addiction will be more. In addition, among the studied subjects, the addicted in three groups (addicted with low involvement, addicted with middle involvement and addicted with high involvement) are different regarding to the power and weakness of the dimensions of the net of healthy as well as the net of unhealthy relations.